Reshaping Employee Experience through Artificial Intelligence: An Analytical Perspective Supported by Real-World Examples - Djedid , Sabrina (Journal of Excellence for Economics and Management Research, 2025)
The professional world is undergoing a major transformation thanks to technological advancements, with artificial intelligence (AI) at the forefront. AI is an effective tool to enhance the employee experience, as it enables organizations to provide personalized and comprehensive support to employees, which boosts job satisfaction, productivity, and fosters long-term creativity and innovation. This analytical study, supported by real-world examples, aims to highlight the potential and innovative solutions that AI offers in reshaping the employee experience. By integrating AI technologies across various stages of the employee journey, organizations have benefited from several advantages, including personalized work environments, automation of routine tasks, improved recruitment processes, enhanced learning and development opportunities, supported interaction and communication, predictive analytics for employee retention, and performance evaluation. These benefits have helped organizations build a workforce ready for the future and create a more attractive work environment. As AI technologies continue to evolve, their role in shaping the future of work and ensuring employee well-being will undoubtedly become even more significant